Influence of electron energy distribution on helium recombining plasma diagnostics using line emissions. Issue 8 (15th August 2017) - Takahashi, H.; Okamoto, A.; Kitajima, S.; Kobayashi, T.; Boonyarittipong, P.; Miura, T.; Nakamura, D.; Kon, J.; Saikyo, T.; Tanaka, Y.; Goto, M.
Abstract : The influence of electron energy distribution on helium recombining plasma diagnostics is investigated using a helium collisional‐radiative model. The population densities of excited helium atoms are calculated for Maxwellian and non‐Maxwellian distribution plasma cases. In the case of the Maxwellian distribution plasma, the electron temperature and electron density determined by the Boltzmann plot method agree well with the input plasma parameters. On the other hand, it is indicated that the electron temperature and electron density are significantly underestimated in the bi‐Maxwellian distribution plasma case, even though the density of the hot electron components is three orders smaller than that of the bulk electrons. This result indicates that in a non‐Maxwellian helium recombining plasma, evaluation of the particle balance based on line emissions from excited helium atoms would be difficult because the reaction rate of atomic and molecular processes is strongly dependent on the electron temperature and density.